2010
DOI: 10.1039/b9nj00660e
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of different nucleotidyl-derivatives as substrates of reactions catalyzed by various HIT-proteins

Abstract: Proteins that have a histidine triad in their active sites belong to the HIT-protein superfamily. They are ubiquitous, are involved in the metabolism of different nucleotides and catalyze their hydrolysis and/or phosphorolysis liberating either the corresponding 5 0 -NMP or 5 0 -NDP, respectively. We studied substrate specificity of nine recombinant HIT-proteins with adenosine 5 0 -phosphosulfate (1), adenosine 5 0 -phosphoramidate (2), adenosine 5 0 -phosphorothioate (3), adenosine 5 0 -phosphorofluoride (4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
3
24
1
Order By: Relevance
“…Recently, Hint enzymes from other organisms (Hint from E. coli and Hint-1 from Arabidopsis thaliana) have been shown to be able to desulfurate the AMPS (46). Conclusion-The discovery of the first phosphorothioate backbone modification of DNA in vivo (10) and the use of synthetic PS-oligos in medicinal applications give rise to questions about the function and metabolism of this modification.…”
mentioning
confidence: 99%
“…Recently, Hint enzymes from other organisms (Hint from E. coli and Hint-1 from Arabidopsis thaliana) have been shown to be able to desulfurate the AMPS (46). Conclusion-The discovery of the first phosphorothioate backbone modification of DNA in vivo (10) and the use of synthetic PS-oligos in medicinal applications give rise to questions about the function and metabolism of this modification.…”
mentioning
confidence: 99%
“…We trust that our findings will be followed by different "omic" experiments to shed more light on the physiological functions of NH 2 -pA and/or its synthetic analog F-pA. Bearing in mind that NH 2 -pA and F-pA are very good substrates for various HIT-proteins that act as nucleoside phosphoramidases (Guranowski et al, 2008(Guranowski et al, , 2010b, we suggest that these ubiquitous proteins may assist in signal transduction from these compounds to factors that control expression of the genes highlighted above. This process might be accompanied by adenylylation of a target molecule and the energy needed for that could come from the splitting of the NeP or FeP bonds.…”
Section: Expression Of Isochorismate Synthase and Accumulation Of Salmentioning
confidence: 87%
“…Recently, we have found the same activity in extracts of mammalian tissues (unpublished) and from yellow lupin seeds (Wojdyła-Mamo n and Guranowski, 2014). The supposition that NH 2 -pA is a ubiquitous compound and that its concentration is enzymatically controlled may be supported by the existence of various proteins that catalyze the cleavage of NH 2 -pA to ammonia and either 5 0 -AMP (pA), by hydrolysis (Kuba et al, 1994;Bieganowski et al, 2002;Guranowski et al, 2010aGuranowski et al, , 2010bGuranowski et al, , 2011Bretes et al, 2013), or 5 0 -ADP (ppA) by phosphorolysis (Guranowski et al, 2010a). Both the synthesis (Wojdyła-Mamo n and Guranowski, 2014) and degradation (Guranowski et al, 2010b) of NH 2 -pA can be controlled by HIT proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stec and co-workers have reported that a human enzyme Fhit (also from the HIT family) is able to conduct the same process [181]. Guranowski et al studied activity of nine recombinant HIT proteins towards AMPS [211]. The proteins represented four branches of the HIT superfamily: three Fhit proteins (human, Arabidopsis thaliana, and Trypanosoma brucei), four Hint proteins (Hint1, Hint3, and Hint4 from A. thaliana, and HinT from Escherichia coli), one decapping protein from Caenorhabditis elegans, and aprataxin-like protein from A. thaliana.…”
Section: Phosphorothioate Analogs [Mix-ps]- [All-(r P )-Ps]-and [Amentioning
confidence: 98%